Adiposity Is a Key Correlate of Circulating Fibroblast Growth Factor-21 Levels in African Males with or without Type 2 Diabetes Mellitus. (12th September 2018) - Mashili, Fredirick L.; Ramaiya, Kaushik; Lutale, Janet; Njelekela, Marina; Francis, Filbert; Zierath, Juleen; Krook, Anna
Abstract : Background . Fibroblast growth factor-21 is an endocrine regulator with therapeutic and diagnostic potential. The levels and pattern of circulating FGF-21 have been described mainly in European and Asian populations. Given its strong association with adiposity, and the reported ethnic variabilities in body composition, examining FGF-21 in an African population is crucial. Methods . We measured levels of circulating FGF-21 in 207 overweight and obese Tanzanian males with or without type 2 diabetes mellitus (T2DM), and using statistical approaches, we explored their relationship with anthropometric and biochemical parameters. Results . Consistent with previous reports from European and Asian populations, we found higher levels of FGF-21 in people with T2DM compared to those without the disease. Based on statistical models, measures of adiposity explained up to 59% of the variability in FGF-21 levels in the circulation. Conclusion . Levels of circulating FGF-21 in overweight and obese African males are higher in T2DM and strongly correlate with measures of adiposity.